The Impact Of Zakat Accounting Standard (Safs Sharia No.109) On The Performance Of Zakat Institutions In Indonesia - Pamuncak, Mohammad Bintang; Possumah, Bayu Taufiq; Halim, Zairihan Abdul (The journal of contemporary issues in business and government, 2021)
This paper aims to examine the influence of accounting standards (SAFS Sharia No.109) for zakat on the financial performance of zakat institutions. This study has employed Difference in Difference (DiD) test and Panel data regression in order to achieve the objective of study. This study found that there is a difference in zakat institution performance between the pre and post adoption of SAFS in the DiD test. However, panel regression results show that there is no significant change in the adoption of SAFS Sharia No.109 to the zakat institution financial performance. A plausible reason for insignificant relation is that SAFS Sharia No.109 has not yet faithfully adhered by zakat institutions in their reporting, particularly with respect to the zakat for productive purpose (Alim, 2015). On the other hand, this study also found that zakat fund collection and zakat institution equity have significant impact on the performance of zakat institutions in Indonesia.